Interleukin-6 receptor blockade in patients with COVID-19: placing clinical trials into context. Issue 6 (June 2021) - Angriman, Federico; Ferreyro, Bruno L; Burry, Lisa; Fan, Eddy; Ferguson, Niall D; Husain, Shahid; Keshavjee, Shaf H; Lupia, Enrico; Munshi, Laveena; Renzi, Samuele; Ubaldo, Onion Gerald V; Rochwerg, Bram; et al.
Summary: The pleiotropic cytokine interleukin-6 (IL-6) has been implicated in the pathogenesis of COVID-19, but uncertainty remains about the potential benefits and harms of targeting IL-6 signalling in patients with the disease. The efficacy and safety of tocilizumab and sarilumab, which block the binding of IL-6 to its receptor, have been tested in adults with COVID-19-related acute respiratory illness in randomised trials, with important differences in trial design, characteristics of included patients, use of co-interventions, and outcome measurement scales. In this Series paper, we review the clinical and methodological heterogeneity of studies of IL-6 receptor antagonists, and consider how this heterogeneity might have influenced reported treatment effects. Timing from clinical presentation to treatment, severity of illness, and concomitant use of corticosteroids are among the factors that might have contributed to apparently inconsistent results. With an understanding of the sources of variability in these trials, available evidence could be applied to guide clinical decision making and to inform the enrichment of future studies.